Art therapy for patients with depression: expert opinions on its main aspects for clinical practice. (1st November 2016) - Blomdahl, Christina; Gunnarsson, Birgitta A.; Guregård, Suzanne; Rusner, Marie; Wijk, Helle; Björklund, Anita
Abstract: Background : Art therapy is based mainly on clinical experience and is rarely described and evaluated scientifically. There is a need for further exploration of its use in patients with depression. Aim : The aim of this study was to explore what experts consider to be the main aspects of art therapy in clinical practice for patients with depression. Method : Eighteen occupational therapists experienced and educated in art therapy participated. The experts answered three rounds of Delphi questionnaires and ranked their agreement with 74 assertions. Consensus was defined as 70% or higher. Results : The experts agreed more on assertions about theoretical frames of reference than about clinical practice. The main aspects of art therapy were agreed to be the patients' opportunity to express themselves verbally and through making art. It was equally important that art tasks provided an opportunity to address depressive thoughts, feelings, life experiences, and physical symptoms. Conclusions : Experts in the field of art therapy considered that the main aspect of clinical practice in art therapy for patients with depression is that art themes should promote expression related to both to depression and personal history.